Angelina on stage - Craig, Helen; Holabird, Katharine (New York : C.N. Potter : Distributed by Crown Publishers, 1986)
When Cousin Henry gets all the attention in the grown-up musical in which they have roles, Angelina becomes jealous, but she demonstrates her fondness for him when a crisis occurs on opening night.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
School Library Journal
3.8
K-3
Keywords: Theater -- Fiction; Cousins -- Fiction; Mice -- Fiction; Cousins -- Fiction; Mice -- Fiction; Theater -- Fiction